2020
DOI: 10.21203/rs.3.rs-24777/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge regarding 2019 novel coronavirus (2019-nCoV) infection among final year health science students at Arbaminch College of Health Sciences, Southern Ethiopia: a cross-sectional study

Abstract: Introduction In January 2020, World Health Organization declared the outbreak of novel coronavirus a pandemic (global health emergency). The aim of this study was to assess the knowledge about novel coronavirus and its determinant factors among health science students at Arbaminch Health Sciences College, Southwest Ethiopia.Method A cross-sectional study design was employed to assess the level knowledge about novel coronavirus among 304 graduating class students in Arbaminch Health Science College. The study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
4
7
1
Order By: Relevance
“…This study found that most participants had accessed information from new media (TV and radio). This finding is in line with the studies conducted in Addis Zemen District Hospital, 21 Arbaminch Ethiopia, 15 and Egypt. 19 The possible explanation for the similarity is that most participants need easy and accessible ways of getting information.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…This study found that most participants had accessed information from new media (TV and radio). This finding is in line with the studies conducted in Addis Zemen District Hospital, 21 Arbaminch Ethiopia, 15 and Egypt. 19 The possible explanation for the similarity is that most participants need easy and accessible ways of getting information.…”
supporting
confidence: 92%
“…In this study, we found that 82.4% of participants wearing a mask to prevent COVID-19, which in line with the study reported in Arbaminch Ethiopia, 15 and higher than the studies reported in Addis Zemen District Hospital, 21 Paraguay, 27 and Malaysia. 22 The discrepancy might be occurred due to the data collection period.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The studies were conducted from March 2 to June 20, 2020 in different regions of the country. Of those 11 studies, four of them 11 , 16 , 17 , 20 were from multicenters, two studies 10 , 15 were from the Amhara region, three of them 19 , 21 , 23 were from SNNPR, one study 18 was from the Oromia region, and one study 22 was from the Tigray region. All the studies enrolled in this systematic review were cross-sectional studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%